CORRELATION BETWEEN INTERFERON GAMMA RELEASE ASSAY OF ELISPOT METHOD AND CD4+ T LYMPHOCYTE CELL COUNT IN HIV POSITIVE PATIENTS - Ambar, Nabil Salim; Aryati, Aryati; Kusmiati, Tutik; Triyono, Erwin Astha (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Introduction. HIV is a virus that can cause AIDS, which affects the immune system and weakens the body function in fighting disease. The primary cells that HIV attacks are CD4+ T lymphocytes. Opportunistic Infections (OIs) are the biggest risk factors of death in HIV patients and occur in CD4+ T cells <200 cells/μL lymphocytes. TB is a disease with a high mortality rate in the world where Indonesia is a TB endemic country with the highest morbidity rates of TB in the world. The most common OI in people with HIV is TB. The number of limitations on Tuberculin Skin Test (TST) is large, thus in vitro T cells test with (Interferon Gamma Release Assay) IGRA is used in diagnosing latent TB. The aim of this study was to determine the correlation between IGRA ELISPOT method and CD4+ T lymphocyte cell count in HIV positive patients.Method. This was an observational analytical study with cross sectional design. The number of samples was 56 HIV positive patients who were treated at the UPIPI Clinic of the Dr Soetomo Surabaya Hospital. The examination of CD4+ T lymphocyte count was perfomed with FACSCalibur and IGRA was examined with T-SPOT.TB. The results were analyzed using Spearman correlation test.Results. CD4 + lymphocyte cell counts based on WHO groupings were as follows: > 500 cells / μL (33.92%), 200-349 cells / μL (25%), 350-499 cells / μL (25%) and <200 cells / μL (16 , 07%). IGRA examination results showed 35.18% positive and 64.81% negative. The grouping of CD4+ T lymphocyte cell counts based on IGRA test results was 27.77% with positive IGRA and 48.14% with negative IGRA. Spearman correlation test between CD4+ T cell lymphocytes with IGRA in HIV positive patients showed r = 0,036 (p = 0,794).Conclusion. There was no correlation between interferon gamma release assay of ELISPOT method and CD4+ T lymphocyte cell count in HIV positive patients.